In-situ boron-induced grain refinement and its impact on the metallurgical and mechanical properties of Ti6Al4V alloy processed by laser powder bed fusion - Hizli, Huseyin (2025)
This PhD thesis investigates the role of boron-modified Ti6Al4V alloys fabricated using Powder Bed Fusion – Laser Beam in achieving in-situ grain refinement and enhanced mechanical properties. Through the incorporation of both amorphous and crystalline boron, this research explores the resulting microstructural evolution, phase transformation, and mechanical performance. Key findings demonstrate that even a small addition of boron (0.1 wt.%) significantly refines the grain structure of Ti6Al4V alloys, transitioning from coarse, columnar grains to a more desirable equiaxed morphology. This refinement is particularly critical for overcoming the anisotropic mechanical properties commonly associated with additively manufactured titanium alloys.